06 Media's Role in the Public Opinion - Elda KATORRI (Association of Social and Educational Innovation, 2014)
The public opinion has always existed, but its echo and influence has been increased and amplified by the tools of mass communication. The latter have extended the field of their activities from a space and time perspective, by playing a basic role in the development of democracy. The purpose of our research is to emphasize the fact that the role of media, that is, radio, television, press and internet is essential to the creation and amplification of the public opinion. The use, misuse and deformation this media imposes on words, image or sound plays a key role in the crystallization of the public opinion. To dwell on this influence and explain it in practice, we have brought forth a survey conducted with the faculty students, the youngest users of these media.